Facile bioactive transformation of magnesium alloy surfaces for surgical implant applications - Wang, Cheng-Chieh; Hung, Jing-Ya; Uan, Jun-Yen; Fang, Chih-Yuan; Kuo, Yu-Lin; Chang, Wei-Jen; Ohiro, Yoichi; Sun, Ying-Sui (Frontiers in Bioengineering and Biotechnology, 2023)
The market for orthopedic implant alloys has seen significant growth in recent years, and efforts to reduce the carbon footprint of medical treatment (i.e., green medicine) have prompted extensive research on biodegradable magnesium-based alloys. Magnesium alloys provide the mechanical strength and biocompatibility required of medical implants; however, they are highly prone to corrosion. In this study, Mg-9Li alloy was immersed in cell culture medium to simulate degradation in the human body, while monitoring the corresponding effects of the reaction products on cells. Variations in pH revealed the generation of hydroxyl groups, which led to cell death. At day-5 of the reaction, a coating of MgCO3 (H2O)3, HA, and α -TCP appeared on sample surfaces. The coating presented three-dimensional surface structures (at nanometer to submicron scales), anti-corrosion effects, and an altered surface micro-environment conducive to the adhesion of osteoblasts. This analysis based on bio-simulation immersion has important implications for the clinical use of Mg alloys to secure regenerated periodontal tissue.